Green IoT for Precision Agriculture: Reducing Water and Energy Usage through Real-Time Monitoring and Feedback Systems - Budi Artono; Imam Iunaedi; R. Oktav Yama Hendra; Tri Lestariningsih (International Forum of Researchers and Lecturers, 2024)
The integration of Green Internet of Things (Green IoT) systems in agriculture presents a promising solution for addressing critical challenges in water and energy usage. This study investigates the impact of real-time monitoring and data-driven irrigation control on resource optimization in precision agriculture. By incorporating soil moisture sensors, solar-powered IoT devices, and data analytics, the system aims to reduce water and energy consumption, enhancing sustainability in farming practices. The research finds that the Green IoT system can reduce water usage by up to 40% compared to traditional methods, while energy consumption is decreased by approximately 25% through the use of solar energy. The study also explores the advantages of implementing IoT-enabled systems, which ensure precise water delivery, preventing over-watering and under-watering, thereby improving crop yields and reducing waste. Despite these positive outcomes, the research identifies key challenges such as high initial costs, limited infrastructure in rural areas, and concerns related to data security. These barriers hinder the widespread adoption of Green IoT systems, especially in developing agricultural regions. Nonetheless, the findings highlight the potential of Green IoT to foster sustainable agricultural practices by promoting efficient resource use and reducing environmental impact. The study suggests that further research should explore the long-term economic implications of Green IoT adoption and investigate ways to overcome technical and financial challenges. Additionally, expanding the scope of Green IoT to other agricultural sectors, such as livestock farming, could enhance its applicability and overall impact on agricultural sustainability.